the essensial of family medicine - philip de sloane, lisa m slatt (the point, 2007)
Preface The fifth edition of Essentials of Family Medicine continues our tradition of providing learners with a state-of-the-art guide to the field. New features for this edition include Continued focus on an evidence-based approach to care, with chapters on Information Mastery: Basing Care on the Best Available Evidence, extensive rating of the strength of evidence supporting recommendations, and, where appropriate, algorithms outlining general approaches to common problems. New chapters on venous thromboembolism, liver disease, cognitive impairment, and relationship issues. A comprehensive introduction to the principles and science base of family medicine, and the role of the specialty in the U.S. healthcare system. A bank of web-based multiple choice questions, called Examkit, linked to the chapters. Faculty can use these questions to generate customized examinations. A web-based self-assessment for students to test their understanding of material presented in the text. Essentials of Family Medicine is meant to be read from cover to cover and used as a basic reference by students doing third- and fourth-year clerkships in family medicine. Other professionals, including specialists in other fields, residents in family medicine, physicians' assistants, and nurse practitioners, have used it as a comprehensive introduction to the field. We hope our readers find it useful and easy to read. As always, we welcome comments, corrections, and suggestions for the next edition. Please address them to Philip Sloane or Lisa Slatt in care of Department of Family Medicine, Aycock Building, CBQ 7595, University of North Carolina, Chapel Hill, NC 27599. Finally, we'd like to thank the people who have helped put this edition together. The list must include, first and foremost, our author-colleagues, who drafted chapters while pursuing busy clinical and academic lives. Special recognition goes to the outstanding efforts of Dr. Judy Washington and Dr. Chantal Brazeau, who served as editors for Examkit questions. In addition, key assistance has been provided by Linda Allred, Mary Roederer, and our editorial team at Lippincott Williams & Wilkins, including Donna Balado, Cheryl Stringfellow, Emilie Moyer, Jennifer Kuklinski, and Tenille Sands. Philip D. Sloane Lisa M. Slatt Mark H. Ebell Louis B. Jacques Mindy A. Smith